1 Henry A. Bullard & Thomas Curry, A New Digest of the Statute Laws of the State of Louisiana 252 (1842) - (:unkn) unknown (My University, 1842)
59: Prohibited the carrying of " any concealed weapon, such as a dirk, dagger, knife, pistol, or any other deadly weapon." Punishable by fine of $20-50.
Keywords: CARRY - CONCEALED